Where does meniscal damage progress most rapidly? An analysis using three-dimensional shape models on data from the Osteoarthritis Initiative. Issue 1 (January 2018) - Dube, B.; Bowes, M.A.; Kingsbury, S.R.; Hensor, E.M.A.; Muzumdar, S.; Conaghan, P.G.
Summary: Objectives: Meniscal pathology is integral to knee osteoarthritis (OA) and its progression; it provides a progression biomarker and a potential treatment target. Magnetic resonance imaging (MRI) demonstrates large heterogeneity in meniscal damage; this structural complexity means measurement is difficult. The aim of this study was to apply novel 3D image analysis to determine which meniscal pathologies demonstrated most change during OA progression. Methods: Knee images were selected from the progression cohort of the Osteoarthritis Initiative choosing participants with risk factors for medial OA progression. Medial and lateral menisci were manually segmented then analysed using a statistical shape model of the tibia as a reference surface. Responsiveness was assessed at 1 year using standardised response means (SRMs) for four constructs: meniscal volume, extrusion volume, thickness and tibial coverage; anatomical sub-regions of these constructs were also explored. Results: Paired images from 86 participants (median age 61.5, 49% female, 56% obese) were included. Reliability of the novel meniscal measurements was very good intraclass correlation coefficients (ICCs all > 0.98). Meniscal volume and extrusion demonstrated no significant change. Moderate responsiveness was observed for medial meniscus thickness (SRM −0.35) and medial tibial coverage (SRM −0.36). No substantial change was seen for the lateral meniscus measures. Sub-region analysis did not improve responsiveness; while greater change was seen in the posterior medial compartment, it was associated with increased variance of the change. Conclusions: The location of meniscal damage was consistently in the posterior medial region, and two measurements (thickness and tibial coverage) were most responsive. Meniscal measures should add to discriminatory power in OA progression assessment.